Increasing social sciences learning achievement and activeness through course review horay model - Agustinus Ufie; Ferdinand Solomon Leuwol; Aprilia Beatrix Mainake (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2020)
This study aims to increase the activeness and learning achievement of social sciences using the Course Review Horay learning model. The subjects in this research were the 4th grade students at SD Inpres 42 Ambon, with the total of 21 people. The method used in this research was Classroom Action Research, carried out in two cycles with four stages including plan, implementation, observation, and reflection. The data collection techniques used were observation, interviews, learning outcomes tests for each cycle, and documentation. Qualitative and quantitative analysis were used to analyze the data of this research. The research results indicated that there was enhancement in the students’ learning outcomes because of their seriousness and activeness in participating using the Course Review Horay learning approach. The Course Review Horay learning model is very well to use in the social sciences learning process since this model makes a festive learning atmosphere.